Role of aspartate ammonia-lyase in Pasteurella multocida - Zui Wang; Li Li; Peng Liu; Chen Wang; Qin Lu; Lina Liu; Xiaozhong Wang; Qingping Luo; Huabin Shao (BMC Microbiology, 2020)
Abstract Background Pasteurella multocida is responsible for a highly infectious and contagious disease in birds, leading to heavy economic losses in the chicken industry. However, the pathogenesis of this disease is poorly understood. We recently identified an aspartate ammonia-lyase (aspA) in P. multocida that was significantly upregulated under iron-restricted conditions, the protein of which could effectively protect chicken flocks against P. multocida. However, the functions of this gene remain unclear. In the present study, we constructed aspA mutant strain △aspA::kan and complementary strain C△aspA::kan to investigate the function of aspA in detail. Result Deletion of the aspA gene in P. multocida resulted in a significant reduction in bacterial growth in LB (Luria-Bertani) and MH (Mueller-Hinton) media, which was rescued by supplementation with 20 mM fumarate. The mutant strain △aspA::kan showed significantly growth defects in anaerobic conditions and acid medium, compared with the wild-type strain. Moreover, growth of △aspA::kan was more seriously impaired than that of the wild-type strain under iron-restricted conditions, and this growth recovered after supplementation with iron ions. AspA transcription was negatively regulated by iron conditions, as demonstrated by quantitative reverse transcription-polymerase chain reaction. Although competitive index assay showed the wild-type strain outcompetes the aspA mutant strain and △aspA::kan was significantly more efficient at producing biofilms than the wild-type strain, there was no significant difference in virulence between the mutant and the wild-type strains. Conclusion These results demonstrate that aspA is required for bacterial growth in complex medium, and under anaerobic, acid, and iron-limited conditions.